Size-controlled emission of long-time durable CsPbBr3 perovskite quantum dots embedded tellurite glass nanocomposites - Erol, Erdinc; Kibrisli, Orhan; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ELSEVIER SCIENCE SA, 2020)
Among various semiconductor quantum dot materials, all-inorganic CsPbBr3 perovskite quantum dots (PQDs) are at the center of ongoing research with their excellent optical properties. However, poor durability of CsPbBr3 PQDs under ambient conditions, e.g. oxygen, heat, moisture, light-exposure, results in keeping them away from long-term practical applications. One of the most promising approaches to improve their durability is the preservation of CsPbBr3 PQDs in oxide glass hosts. Therefore, in this study, CsPbBr3 PQDs are successfully embedded inside a tellurite-based glass via melt-quenching and subsequent heat-treatment. Pure cubic structure of CsPbBr3 PQDs is confirmed by X-ray diffraction analysis. Radii of PQDs are tuned in the range of 2.36-4.89 nm and emission color modulation between 469 and 520 nm with narrow full width at half maximum values of 16-23 nm is realized by band gap tailoring from 3.03 eV to 2.41 eV through rigorous heat-treatment procedures. CsPbBr3 PQDs exhibit superior thermal and chemical durability and impressively stable photoluminescence properties due to strong protection of tellurite glass host. Consequently, excellent long-term durability along with highly pure and tunable emission colors of CsPbBr3 PQDs embedded tellurite glass nanocomposites may lead the way of these outstanding materials through practical photonic and opto-electronic applications.
Keywords: CsPbBr3; Perovskite quantum dots; Tellurite glass; Durability; Size control; Tunable emission; CESIUM LEAD HALIDE; LIGHT-EMITTING-DIODES; OPTICAL-PROPERTIES; THERMAL-STABILITY; DEFECT-TOLERANCE; ANION-EXCHANGE; NANOCRYSTALS; CSPBX3; PHOTOLUMINESCENCE; LUMINESCENCE; Engineering